Multirepresentation in Physics Learning Research: A Content Analysis Review of Trends, Opportunities, and Challenges - Ate, O; Parno, P.; Munfaridah, N (Journal of Science Education Research, 2025)
The study aimed to present the trends, opportunities, and challenges of using multiple representation in physics learning from Junior High School to Higher Education. Through the Content Analysis method, this study analyzed 45 journals that examined of using multiple representation in physics learning obtained using Publish or Perish with Google Scholar and Scopus databases from 2019-2023. The results showed that the number of publications of using multiple representation has increased. The most widely used research type was quantitative. High school students and materials (waves and motion) were the target research subjects and popular materials. Learning physics using multiple representations has the opportunity to facilitate students' concept understanding, problem solving ability, and representation ability. The challenges faced in its use are teachers' difficulties in organizing representations in a structured and coherent manner, as well as students' difficulties in representing physics concepts in graphics and equations. In relation to these findings, it is suggested that future researchers adopt qualitative research and increase the diversity of physics subjects and topics. Also, the abilities measured, such as students' thinking and cognitive explore multiple representation in physics learning. Future research could explore the potential of digital technology and qualitative approaches to use multiple representation to enrich the quality of physics education.